TRANSLATING THE INTRANSLATABLE: STYLISTIC SHIFTS IN THE UZBEK TRANSLATION OF ENGLISH LITERARY TEXTS - Dilnoza Kurbanbayeva Sheripbay qizi (World Scientific Research Journal, 2025)
Abstract: In the process of translation, the translation of literary texts into Uzbek includes not only the meaning of words, but also their methodological features. In the translation of literary works in English into Uzbek, a change in stylistic means is especially important. Sometimes it becomes difficult to fully and accurately translate the methodological elements present in English into Uzbek. In this case, the translator, relying on his creative approach and knowledge of the language, refers to stylistic changes in order to preserve the meaning and tone expressed in the original text.